PERAN KOMISI YUDISIAL DALAM MENJAGA INDEPENDENSI KEKUASAAN KEHAKIMAN DI INDONESIA: Darma Rizki Maulana, Nur Laelatul Qomaria, Sintiyana, Widianti Nor Nabila - Darma Rizki Maulana (As-Shahifah : Journal of Constitutional Law and Governance, 2025)
The Judicial Commission is an independent state institution constitutionally mandated to uphold the honor, dignity, and integrity of judges. This article aims to analyze the role of the Judicial Commission in maintaining the independence of judicial power in Indonesia, while also identifying the challenges it faces in carrying out its functions and authorities. This study employs a normative juridical method with statutory and conceptual approaches. The findings indicate that the Judicial Commission plays a significant role in the ethical supervision of judges, although it still encounters obstacles such as overlapping authority with the Supreme Court, limitations in investigative powers, and political interference in the recruitment process of Supreme Court justices. Therefore, it is necessary to strengthen the legal foundation and authority of the Judicial Commission so that it can effectively fulfill its mandate within the Indonesian constitutional system.